An Algorithm for Isolating the Real Solutions of Piecewise Algebraic Curves - Jinming Wu; Xiaolei Zhang (Journal of Applied Mathematics)
The piecewise algebraic curve, as the set of zeros of a bivariate spline function, is a generalization of the classical algebraic curve. In this paper, an algorithm is presented to compute the real solutions of two piecewise algebraic curves. It is primarily based on the Krawczyk-Moore iterative algorithm and good initial iterative interval searching algorithm. The proposed algorithm is relatively easy to implement.